Bishop Gsell / Jessie Litchfield. - Litchfield, Jessie, 1883-1956.
Bishop Gsell outside the Roman Catholic Presbytery, Smith Street. Gsell came to the Territory in 1907 to establish a mission on Bathurst Island, and was later appointed Bishop of Darwin. Date: Unknown